Evaluating solar and wind electricity production in the Kingdom of Bahrain to combat climate change - Alnaser, N. W.; Alnaser, W. E.; Al-Kaabi, E. A. D. (Frontiers in Built Environment, 2023)
Recently, the Kingdom of Bahrain doubled its renewable energy (RE) target to achieve 20% of energy mix by 2035 instead of 10%. Two RE sources are candidates among others, i.e., solar and wind energy. Both of these sources require, relatively, large spaces, and both are subject to fluctuation throughout the day, month, and year. Therefore, a thorough experimental evaluation of these two sources is necessary as theoretical assessment has been extensively made. Therefore, we are analyzing the result of two prototypes, solar and wind RE systems installed by the government. The first system includes installing two wind turbines (WT1 and WT2), each rated at 850 kW, and the second system is a 1 MW solar PV system. The annual result for 2022 is recorded for the wind turbine along with the results of 2 years (2017 and 2018) for the solar PV. The annual average produced by the first turbine (WT1), in the front, was found to be 899 MWh, while the second (WT2), at the back, was 872 MWh with an average capacity factor of 12%. Meanwhile, the 1 MW solar PV produced 1,632 MWh in 2017 and 1,497 MWh in 2018. Our analysis shows that each kW of wind turbine yields 2.9 kWh per day while each kW solar PV electricity yields, in average, 4.3 kWh per day. We also found that the average cost of wind electricity unit is 49 fils/kWh (USD¢ 13/kWh) and the payback is nearly 40 years while the average cost of solar electricity unit is 17 fils/kWh (USD ¢ 4.5/kWh) and the payback is nearly 12 years. Furthermore, we found that 1 MW of solar PV gives more electricity than 1 MW of wind by 42% and, subsequently, alleviates more CO2 by 42% than wind turbines’ installation; i.e., 1 MW solar PV will annually produce 1,500 MWh (alleviating 654 tons of CO2), while 1 MW produces, annually, 1057 MWh (alleviating 461 tons of CO2).